2014
DOI: 10.1021/jp500558x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Diethyl 2,5-Dioxahexane Dicarboxylate and Polyethylene Carbonate as Decomposition Products of Ethylene Carbonate Based Electrolytes by Fourier Transform Infrared Spectroscopy

Abstract: The formation of passive films on electrode by electrolyte decomposition plays a crucial role in maintaining the reversibility of Li ion batteries (LIBs); however the understanding of the electrolyte decomposition process is still lacking. In this study, we investigated the decomposition of an electrolyte based on ethylene carbonate (EC) solvent, and identified the decomposition products on Sn and Ni surface by matching the IR spectra to that of synthesized reference compounds. The reference compounds diethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 34 publications
(87 reference statements)
2
46
0
Order By: Relevance
“…These bands were also found in the 1 st delithiation cycle when approaching OCP and they can be attributed to polyethylene carbonate. Similarly, Shi et al 48 showed the formation of this species using EC-based electrolyte over Ni-electrodes. This suggests that SEI film formation in the absence of FEC is somewhat potential-dependent.…”
Section: Resultsmentioning
confidence: 81%
“…These bands were also found in the 1 st delithiation cycle when approaching OCP and they can be attributed to polyethylene carbonate. Similarly, Shi et al 48 showed the formation of this species using EC-based electrolyte over Ni-electrodes. This suggests that SEI film formation in the absence of FEC is somewhat potential-dependent.…”
Section: Resultsmentioning
confidence: 81%
“…Indeed, reduction products of linear carbonates are known to be responsible for changes in electrolyte composition over time; [1][2][3][4][5][6][7][8] the generated alkoxide can trigger the chemical formation of soluble oligomers through consumption of linear and cyclic carbonates, which can explain the decay in battery performance. Indeed, reduction products of linear carbonates are known to be responsible for changes in electrolyte composition over time; [1][2][3][4][5][6][7][8] the generated alkoxide can trigger the chemical formation of soluble oligomers through consumption of linear and cyclic carbonates, which can explain the decay in battery performance.…”
Section: Resultsmentioning
confidence: 99%
“…1,2,3 The electrolytes used for LIBs are normally composed of highly polar solvents such as carbonate derivatives 4,5,6 or poly(ethylene oxide) (PEO) and lithium salts such as LiPF 6 (LiTFSI), 7 Li[N(SO 2 C 2 F 5 ) 2 ] (LiBETI) 8 etc. Lithium bis(trifluoromethane) sulfonamide (LiTFSI) was first brought to the application of lithium ion electrolytes by Armand.…”
Section: Introductionmentioning
confidence: 99%